2023
DOI: 10.1109/access.2023.3235209
|View full text |Cite
|
Sign up to set email alerts
|

RECLAIM: Renewable Energy Based Demand-Side Management Using Machine Learning Models

Abstract: The diesel generators sets (DGs) and battery storage systems (BSS) are the essential energy sources in a modern high-rise buildings. In this paper DG, BSS and Photovoltaic system (PV) has been considered to minimize the grid power injection using a centralized Energy Management System (EMS). Machine Learning (ML) techniques are used to predict the performance of various regression models by comparing grid power and load curves. It includes Artificial Neural Network (ANN), Wide Neural Network (WNN), Linear Regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…This methodology is characterized not only by its capability to enable optimal energy scheduling but also by its substantial reduction in communication overhead while maintaining stringent data privacy. A regression analysis-based DSMS has been proposed in the centralized EMS framework for minimizing grid power injection and maximizing the efficiency of hybrid energy sources [96].…”
Section: Ml-based Dsmsmentioning
confidence: 99%
“…This methodology is characterized not only by its capability to enable optimal energy scheduling but also by its substantial reduction in communication overhead while maintaining stringent data privacy. A regression analysis-based DSMS has been proposed in the centralized EMS framework for minimizing grid power injection and maximizing the efficiency of hybrid energy sources [96].…”
Section: Ml-based Dsmsmentioning
confidence: 99%
“…In addition to the studies referred to in [30], [31], [32], [33], [34], [35], [36], [37], [38], [39], [40], [41], [42], [43], [44], [45], [46], [47], [48], [49], [50], [51], [52], [53], [54], [55], [56], [57], [58], [59], [60], [61], [62], [63], and [64], there are also studies in which artificial intelligence is included in the effective use of energy efficiency and renewable energy resources. A centralized energy management system (EMS) and machine learning models were employed to optimize the use of PV, DG, and BESS, with the goal of minimizing grid power injection and maximizing the usage of HRES [65]. The results showed that Regression Coarse Tree and Linear Regression methods give better results than other machine learning techniques in reducing peak demand and maximizing the utilization of HRES.…”
Section: Research Background Synopsismentioning
confidence: 99%
“…Bilgic et al (2023) reviewed artificial neural network advances in hydrogen production research [22]. Asghar et al (2022) integrate demand side management techniques with various machine learning methods in a hybrid energy source system [23]. Yao et al (2023) introduce key performance indicators for the comparison of machine learning workflows for energy research and evaluate the advances in the application of machine learning methods in energy management, storage, harvesting, and conversion [24].…”
Section: Hybrid Renewable Energy Applicationsmentioning
confidence: 99%